Nigella sativa plant extract inhibits the proliferation of MDA-MB-231 breast cancer cells via apoptosis and cell cycle arrest (Bangladesh Journal of Pharmacology, 2024)
The study was designed to evaluate the antiproliferative effects of Nigella sativa plant ethanol extract against MDA-MB-231 triple-negative breast cancer cells. DAPI and annexin V/propidium iodide staining assays were used to examine apoptosis. Results showed that N. sativa extract significantly (p